PREGNANCY, THYROTOXICOSIS AND POLYMYOSITIS - Hafeez, Muhammad; Sarfraz, Tariq; Azhar, Muhammad; Khan, Raja Ghayas; Tariq, Humaira (Journal of Ayub Medical College Abbottabad, 2015)
A young pregnant lady of 26 years age, presented with recent onset weakness of legs. On examination, she was only able to move legs from side to side and lift the arms with difficulty. Rest of neurological and systemic examination did not reveal any abnormality. On investigations, there were raised serum muscle enzyme levels, hyperthyroid hormone profile, myopathy on electromyography and myositis on muscle biopsy. Common conditions of myositis were excluded. She was given glucocorticoids and methimazole to which she responded well.